CALCULATION OF CANAL LOSSES IN NIRA LEFT BANK CANALAND SUITABLE METHOD TO REDUCE IT - N. J. SATHE; A. S. NAGAWADE; S. S. NIKAM (International Journal of Innovations in Engineering Research and Technology, 2021)
Water is a very precious natural resource. When this precious resource moves through the canals certain part of the water is lost by seepage, evaporation etc. This loss is known as conveyance loss. In present paper, study of Nira Left Bank Canal (NLBC) is donewhich is situated in Pune district. Total length of canal is 162 Km out of which 30 Km is our study area. Dischargecalculations at the head of canal and at 30thKm is done, two standing wave flumesare present at these two locations.Percentage loss in discharge is calculated and to reduce these losses Cement Concrete Lining is suggested.Lining design is done based upon IS 10430:2000.Due to lining section of canal will get enlarged and discharge carrying capacity also getsincrease which will result in increasing intensity of irrigation.At present,discharge carrying capacity of canal is 20.39 cumecandarea to be irrigated is only 45 percentage of the available area so irrigable area can be enhanced by lining. Cost estimate of lining is done and benefit cost ratio of project is calculated